Association between continued residence in temporary prefabricated housing and musculoskeletal pain in survivors of the Great East Japan Earthquake: a longitudinal study - Takuya Sekiguchi; Yoshihiro Hagiwara; Yumi Sugawara; Yutaka Yabe; Eiji Itoi; Ichiro Tsuji; Yasuhito Sogi; Masahiro Tsuchiya; Masashi Koide; Nobuyuki Itaya; Shinichirou Yoshida; Toshihisa Yano (BMJ Open)
Objective Prolonged periods of living in prefabricated houses (PHs) may increase the risk of musculoskeletal (MSK) symptoms; however, the association is not clear. This study aimed to investigate the association between continued residence in PHs and MSK pain in a population affected by a natural disaster, the Great East Japan Earthquake (GEJE) survivors.Design, setting and participants A panel study was conducted including 1059 and 792 survivors at 2 and 4 years, respectively, after the GEJE, using a self-reported questionnaire. Those with no response on living status and those who did not live in a PH were excluded. Participants were classified into two groups by living status: continued residence in a PH (lived in a PH during both periods) or moving out of a PH (lived in a PH in the first period and did not live in a PH in the second).Primary outcome measure MSK pain included lower back, shoulder, knee, hand or foot, and neck pain. Changes in the occurrence of MSK pain during the two periods were assessed and defined as ‘new-onset’ and ‘continuing’ MSK pain. Multiple logistic regression analysis was used to examine the influence of continued residence in a PH on new-onset and continuing MSK pain.Results Continued residence in a PH was significantly associated with new-onset MSK pain, even after adjustment for covariates (adjusted OR 2.18, 95% CI 1.25 to 3.79, p=0.006). Participants who continued living in a PH had higher rates of continuing MSK pain than those who moved out; however, the difference was not significant (adjusted OR 1.69, 95% CI 0.94 to 3.05, p=0.079).Conclusion Continued residence in a PH was associated with new-onset MSK pain among survivors. Public support should be provided to such people to ensure a more comfortable life.